2016
DOI: 10.1037/pas0000280
|View full text |Cite
|
Sign up to set email alerts
|

Examining potential iatrogenic effects of viewing suicide and self-injury stimuli.

Abstract: The high-stakes nature of self-injurious thoughts and behaviors (SITBs) raises ethical questions and concerns. The authors examined the iatrogenic risk of recently developed behavioral measures such as the suicide or self-injury Implicit Association Tests (IATs), which include repeated and rapid presentation of SITB-related images (e.g., of cut skin) and words (e.g., death, suicide). The impact of these IATs was investigated across a series of 3 studies involving: adult web-based respondents (n = 3,304), under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 21 publications
(26 reference statements)
6
40
0
Order By: Relevance
“…In our analysis, D-scores were not significantly correlated with levels of depression, impulsivity, or inhibition, although there was a trend with state-level anxiety that aligns with the literature on the relationship between suicide attempts and anxiety (Sareen et al, 2005). Lastly, and similar to previous analyses, completion of the S-IAT was not associated with increased levels of sadness or anger or with decreased levels of happiness (Cha et al, 2016). Although the task was associated with decreased anxiety, it is important to note that the S-IAT was conducted at the end of the scanning session, which might have affected these results.…”
supporting
confidence: 88%
“…In our analysis, D-scores were not significantly correlated with levels of depression, impulsivity, or inhibition, although there was a trend with state-level anxiety that aligns with the literature on the relationship between suicide attempts and anxiety (Sareen et al, 2005). Lastly, and similar to previous analyses, completion of the S-IAT was not associated with increased levels of sadness or anger or with decreased levels of happiness (Cha et al, 2016). Although the task was associated with decreased anxiety, it is important to note that the S-IAT was conducted at the end of the scanning session, which might have affected these results.…”
supporting
confidence: 88%
“…Across three intensive suicide research studies, results indicated that participants did not endorse significant increases in suicide risk at postassessment or report adverse events. Collectively, the results add to a body of research demonstrating the feasibility of conducting intensive, nontreatment suicide‐specific research without doing harm to participants (e.g., Cha et al., ; Smith et al., ).…”
Section: Discussionmentioning
confidence: 65%
“…Previous research with civilians suggests that participating in non‐treatment‐related suicide research does not produce significant iatrogenic effects (e.g., Cha et al., ; Gould et al., ). For example, Smith, Poindexter, and Cukrowicz () conducted a study investigating psychiatric and suicide‐specific symptoms and physiological reactivity when exposed to an affectively modulated startle reflex task.…”
mentioning
confidence: 99%
“…Using standard IAT scoring procedures (Greenwald, Nosek, & Banaji, ), associations between ‘death’ and ‘me’ are measured by calculating a difference ( D ) score for each participant; positive D scores indicate a stronger association between death and the self (i.e., faster response latencies on death & me paired trials than on life & me paired trials), whereas negative D scores represent a stronger association between life and the self (see Nock et al., for scoring details). Importantly, iatrogenic effects of self‐injury IATs (i.e., Self‐Injury IAT, Death IAT, Suicide IAT) have been examined in adults, undergraduate students, and adolescent psychiatric inpatients: minimal change in desire for death or self‐injury and only a slight mood decline has been observed from pre‐ to post‐IAT administration (Cha, Glenn et al., ). Therefore, self‐injury IATs, such as the Death IAT, are considered appropriate to use with adolescent clinical populations.…”
Section: Methodsmentioning
confidence: 99%
“…Cha, Glenn et al. () examined iatrogenic effects of a series of IATs (including the Self‐Injury, Suicide, and Death IATs) among adolescent psychiatric inpatients, but did not report specifically on IAT performance. Cha, Augenstein et al.…”
mentioning
confidence: 99%